Different Metabolic Roles for Alternative Oxidase in Leaves of Palustrine and Terrestrial Species - Del-Saz, Nestor Fernandez; Douthe, Cyril; Carriquí, Marc; Ortíz, Jose; Sanhueza, Carolina; Rivas-Medina, Alicia; McDonald, Allison; Fernie, Alisdair R.; Ribas-Carbo, Miquel; Gago, Jorge; Florez-Sarasa, Igor; Flexas, Jaume (Frontiers in Plant Science, 2021)
The alternative oxidase pathway (AOP) is associated with excess energy dissipation in leaves of terrestrial plants. To address whether this association is less important in palustrine plants, we compared the role of AOP in balancing energy and carbon metabolism in palustrine and terrestrial environments by identifying metabolic relationships between primary carbon metabolites and AOP in each habitat. We measured oxygen isotope discrimination during respiration, gas exchange, and metabolite profiles in aerial leaves of ten fern and angiosperm species belonging to five families organized as pairs of palustrine and terrestrial species. We performed a partial least square model combined with variable importance for projection to reveal relationships between the electron partitioning to the AOP (τa) and metabolite levels. Terrestrial plants showed higher values of net photosynthesis (AN) and τa, together with stronger metabolic relationships between τa and sugars, important for water conservation. Palustrine plants showed relationships between τa and metabolites related to the shikimate pathway and the GABA shunt, to be important for heterophylly. Excess energy dissipation via AOX is less crucial in palustrine environments than on land. The basis of this difference resides in the contrasting photosynthetic performance observed in each environment, thus reinforcing the importance of AOP for photosynthesis.